(untitled) (Research, Society and Development, 2024)
Introduction: Depression has significantly affected the elderly population, with symptoms such as altered sleep, reduced appetite, pain and other physical symptoms. Factors such as loss of functionality and changes in quality of life contribute to this prevalence. In addition, Primary Health Care faces difficulties in diagnosing and treating depression in the elderly. Objective: This narrative review study aims to analyze the different aspects related to depression in the elderly in primary care, covering the areas of promotion, prevention and mental health care. Methodology: This study, a narrative review of the literature, sought to analyze how support programs and social interaction impact on the reduction of depressive symptoms in the elderly in primary care. The search for articles was carried out in the Google Scholar, PubMed, Medline and Scielo databases, with specific inclusion and exclusion criteria. A total of 17 studies were selected for analysis. Results and discussion: Analysis of the articles shows that participation in social support programs and community activities is crucial to reducing depressive symptoms. The evidence found shows that elderly people with greater social involvement have fewer depressive symptoms. Thus, lack of social participation and factors such as family loss and retirement are associated with an increase in the prevalence of depression. Final considerations: This analysis highlights the importance of investing in public policies and community programs that promote social integration and emotional support in order to improve the mental health and quality of life of the elderly.